The preparation of antigen for the generation of polyclonal antibodies against the capsid subunit, VP1, and the viral protease, 3Cpro, of Theiler's murine encephalomyelitis virus (TMEV) - Moetlhoa, Boitumelo (Rhodes University, Faculty of Science, Department of Biochemistry, Microbiology and Biotechnology, 2014)
The Picornaviridae is a family of viruses of economic importance that have a major impact on human and animal health. Some of the major genera found in the Picornaviridae family are Enterovirus which includes Poliovirus (PV) and Human Rhinovirus (HRV), Cardiovirus which includes Theiler's murine encephalomyelitis virus (TMEV) and Saffold virus (SAFV), Aphthovirus of which the Foot and Mouth disease virus (FMDV) is a member and Hepatovirus which includes Hepatitis A virus (HAV). Picornaviruses have a single stranded, positive sense RNA genome which is approximately 7.5-8.4 kb pairs in size. The picornavirus genome is translated into a large polyprotein and is proteolytically cleaved by viral proteases namely 2Apro, 3Cpro and 3CDpro into mature viral structural and non-structural polypeptides encoded by the P1, P2 and P3 domains. Picornaviruses utilise host cell machinery and cellular pathways for entry and uncoating, genome replication and capsid assembly. In our laboratory, we are studying the mechanisms by which TMEV interacts with host cell components and our recent research shows that molecular chaperones are required for a production infection. To follow up on this observation, the overall aim of this study was to prepare antigen for the generation of polyclonal antibodies against the TMEV VP1 and 3Cpro proteins. To this end, the TMEV VP1 and 3Cpro amino acid sequences were analysed to identify hydrophobic, hydrophilic and antigenic regions. Homology modelling was performed in order to predict linear B cell epitopes exposed on the surface of the protein structures. The full length coding sequences of VP1 and 3Cpro were selected for amplification by the PCR and cloning into pQE-80L for expression in a bacterial system. Time course induction studies of recombinant VP1 and 3Cpro showed that the proteins were maximally expressed at 6 hrs and 4 hrs respectively. Recombinant VP1 was solubilised using the detergent, Sarcosyl and purified by Nickel affinity chromatography under native conditions. Because recombinant VP1 co-purified with an unidentified protein, the pET expression system was used. Although no protein of the estimated size was observed by SDS-PAGE analysis in the time course induction study, Western analysis using anti-His6 (2) antibodies detected a signal of ~35 kDa. Solubility studies resulted in the presence of two protein bands in the insoluble fraction resolved between 35 and 40 kDa. Recombinant 3Cpro expressed in a bacterial system was predominantly present in the insoluble fraction. Treatment with Sarcosyl had no effect on the solubility of the recombinant protein and it was therefore purified under denaturing conditions using 8M urea. Following dialysis, 3Cpro was used for immunisation of rabbits. Crude anti-TMEV 3Cpro antibodies were able to detect as little as 107 ng of bacterially expressed antigen at a dilution of 1:100 000 by Western analysis. The presence of contaminating proteins was reduced using pre-cleared anti-TMEV 3Cpro antibodies. The antibodies were unable to detect virally expressed 3Cpro in BHK-21 cell lysate supernatant. In an attempt to determine whether TMEV 3Cpro is present in the insoluble fraction, anti-TMEV 3Cpro antibodies were tested using total protein prepared from infected and mock-infected cell lysates. Once again, no protein band the size of 3Cpro was detected. The antibodies were further tested for detection of 3Cpro in TMEV-infected cells by indirect immunofluorescence and confocal microscopy. A diffuse cytoplasmic and perinuclear distribution, as well as nuclear staining, was observed in infected BHK-21 cells. This staining pattern resembled that observed for the HRV, FMDV and EMCV 3Cpro in similar experiments. Further experiments are required to confirm specificity of these antibodies for virally-expressed 3Cpro by Western analysis and indirect immunofluorescence.
Keywords: Enteroviruses; Encephalomyelitis; Antigens